If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 + 3(x + -6) = 23 Reorder the terms: 2x + 1 + 3(-6 + x) = 23 2x + 1 + (-6 * 3 + x * 3) = 23 2x + 1 + (-18 + 3x) = 23 Reorder the terms: 1 + -18 + 2x + 3x = 23 Combine like terms: 1 + -18 = -17 -17 + 2x + 3x = 23 Combine like terms: 2x + 3x = 5x -17 + 5x = 23 Solving -17 + 5x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 5x = 23 + 17 Combine like terms: -17 + 17 = 0 0 + 5x = 23 + 17 5x = 23 + 17 Combine like terms: 23 + 17 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 | | x=(2.4e)/(0.68^1/5) | | 3/5*4/7*1/3 | | -9x^2+16x-14=0 | | 5(2x+3)=7(x+1) | | 0.11+0.09+720=1520 | | 17x+27x=180 | | 9/10*5/7*1/3 | | -16+2x=4x-4(4+3) | | 4x^2-15x+14=-6x+9 |